T-cell activation Rho GTPase-activating protein maintains intestinal homeostasis by regulating intestinal T helper cells differentiation through the gut microbiota - He, Ruirui; Chen, Jianwen; Zhao, Ziyan; Shi, Changping; Du, Yanyun; Yi, Ming; Feng, Lingyun; Peng, Qianwen; Cui, Zhihui; Gao, Ru; Wang, Heping; Huang, Yi; et al. (Frontiers in Microbiology, 2023)
Common variants of the T-cell activation Rho GTPase-activating protein (TAGAP) are associated with the susceptibility to human inflammatory bowel diseases (IBDs); however, the underlying mechanisms are still unknown. Here, we show that TAGAP deficiency or TAGAP expression downregulation caused by TAGAP gene polymorphism leads to decreased production of antimicrobial peptides (AMPs), such as reg3g, which subsequently causes dysregulation of the gut microbiota, which includes Akkermansia muciniphila and Bacteroides acidifaciens strains. These two strains can polarize colitogenic T helper cell differentiation in the gut, increase inflammation, and aggravate colitis phenotype in mice. More importantly, we demonstrated that recombinant reg3g protein or anti-p40 monoclonal antibody exerted much better therapeutic effects for the treatment of dextran sodium sulfate (DSS)-induced colitis in TAGAP-deficient mice than that in control mice, suggesting that they are potential medicines for human IBD treatment, and they may have a better therapeutic effect for the patients who carry the common variant of TAGAP rs212388.